COVID-19 in Ghana: An Overview of Government Contributions in Fighting this Pandemic - Yeboah Evans; Rose Gyamea Kyeremeh (Quantitative Economics and Management Studies, 2020)
Coronavirus outbreak has brought significant negative impacts on developed and developing economies with Ghana, not an exemption. This pandemic has slow down economic activities across the globe through unplanned budget expenditures by various government. There is an increasing pressure on many governments to directed tremendous capital resource to stop the outbreak. The perspective of this paper is to provide, update, and inform concerning Covid-19 situation in Ghana, and also look at government expenditure on this pandemic and economic impact. This study employed the quantitative method which promotes the analysis of secondary sources of data. The study captured some of economic and livelihood programme implemented by the government of Ghana to support the most vulnerable persons. With Ghana currently having low active Covid-19 confirmed cases proves that the government has done well to control the spread of the virus.